Color and Albedo Heterogeneity of Vesta from Dawn - Reddy, Vishnu; Nathues, Andreas; Le Corre, Lucille; Sierks, Holger; Li, Jian-Yang; Gaskell, Robert; McCoy, Timothy; Beck, Andrew W.; Schröder, Stefan; Pieters, Carle M.; Becker, Kris J.; Buratti, Bonnie J.; et al. (Science, 2012)
Multispectral images (0.44 to 0.98 mm) of asteroid (4) Vesta obtained by the Dawn Framing Cameras reveal global color variations that uncover and help understand the north-south hemispherical dichotomy. The signature of deep lithologies excavated during the formation of the Rheasilvia basin on the south pole has been preserved on the surface. Color variations (band depth, spectral slope, and eucrite-diogenite abundance) clearly correlate with distinct compositional units. Vesta displays the greatest variation of geometric albedo (0.10 to 0.67) of any asteroid yet observed. Four distinct color units are recognized that chronicle processes—including impact excavation, mass wasting, and space weathering—that shaped the asteroid’s surface. Vesta’s color and photometric diversity are indicative of its status as a preserved, differentiated protoplanet.